2022
DOI: 10.1016/j.jviromet.2021.114404
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 PCR test performance on samples stored at ambient temperature

Abstract: The WHO-named Coronavirus Disease 2019 (COVID-19) infection had become a pandemic within a short time period since it was detected in Wuhan. The outbreak required the screening of millions of samples daily and overwhelmed diagnostic laboratories worldwide. During this pandemic, the handling of patient specimens according to the universal guidelines was extremely difficult as the WHO, CDC and ECDC required cold chain compliance during transport and storage of the swab samples. The aim of this study was to compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This suggests that the buffer solution and other components added to the ready-made IA have a better ability to resist interference from temperature, pH changes, and temperature fluctuations. The aforementioned results align with a previous study that utilized Innomed VTM001 virus collection tubes to compare the impact of two distinct storage temperatures (i.e., 22 ± 2°C and 6 ± 2°C) on 30 positive samples by RT-PCR analysis for SARS-CoV-2, finding no false negative results within a span of 6 days for all samples 25. It has been proven that storing selfprepared virus preservation solution in cold storage can make the preservation of viruses more difficult to degrade over a longer period of time.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This suggests that the buffer solution and other components added to the ready-made IA have a better ability to resist interference from temperature, pH changes, and temperature fluctuations. The aforementioned results align with a previous study that utilized Innomed VTM001 virus collection tubes to compare the impact of two distinct storage temperatures (i.e., 22 ± 2°C and 6 ± 2°C) on 30 positive samples by RT-PCR analysis for SARS-CoV-2, finding no false negative results within a span of 6 days for all samples 25. It has been proven that storing selfprepared virus preservation solution in cold storage can make the preservation of viruses more difficult to degrade over a longer period of time.…”
supporting
confidence: 87%
“…The aforementioned results align with a previous study that utilized Innomed VTM001 virus collection tubes to compare the impact of two distinct storage temperatures (i.e., 22 ± 2°C and 6 ± 2°C) on 30 positive samples by RT‐PCR analysis for SARS‐CoV‐2, finding no false negative results within a span of 6 days for all samples. 25 It has been proven that storing self‐prepared virus preservation solution in cold storage can make the preservation of viruses more difficult to degrade over a longer period of time. This finding is supported by the interim guidance on COVID‐19 specimen processing and transportation provided by the Center for Disease Control in the U.S., 26 healthcare professionals should store respiratory specimens at 2–8°C for up to 72 h after collection, or −70°C or lower if testing or transportation was delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Size-fractionated PM samples were collected onto presterilized gelatin filters (Sartorius) at stages 3 to 7/9 of the impactor. The gelatin filters were removed and placed in a clean and sterile holder and were forwarded within 12-72 h for virus testing, which is an acceptable timeframe for specimen transportation and storage 38 . The gelatin filters were dissolved in 600 µl RAV1 buffer of the NucleoSpin RNA Virus kit (Macharey-Nagel, Düren, Germany), and the isolation of viral RNA was carried out following the kit's protocol.…”
Section: Detection and Quantification Of Sars-cov-2mentioning
confidence: 99%
“…Recommendations for the storage and handling of nasopharyngeal swabs typically defer to those specified by the commercial manufacturer [29] . With the ongoing global pandemic and limited supply chain, some laboratories have made modifications to the specified storage conditions for SARS-CoV-2 RNA specimens [87] , [88] , [89] . Evaluations of long-term room-temperature storage condition for nasopharyngeal swabs in viral transport media revealed that samples could be stored for up to 21 days at room temperature without significantly impacting the RT-PCR results [87] .…”
Section: Specimen Handling and Integrity: From Specimen Collection To...mentioning
confidence: 99%